2023
DOI: 10.1186/s12974-023-02840-8
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-derived SerpinA3N promotes neuroinflammation and epileptic seizures by activating the NF-κB signaling pathway in mice with temporal lobe epilepsy

Abstract: Impaired activation and regulation of the extinction of inflammatory cells and molecules in injured neuronal tissues are key factors in the development of epilepsy. SerpinA3N is mainly associated with the acute phase response and inflammatory response. In our current study, transcriptomics analysis, proteomics analysis, and Western blotting showed that the expression level of Serpin clade A member 3N (SerpinA3N) is significantly increased in the hippocampus of mice with kainic acid (KA)-induced temporal lobe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…A recent study showed that the expression level of Serpin E1' family member, SerpinA3N, in the hippocampus of temporal lobe epilepsy mice induced by KA was significantly increased, and it promoted neuroinflammation and seizure by activating NF-κB signaling pathway, suggesting that Serpin family is closely related to epilepsy. 30 Therefore, it is worthy to further explore if initial seizures-induced inflammation elicits elevation of blood Serpin E1 and if its long persistence is implicated in the development or maintenance of DRE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the expression level of Serpin E1' family member, SerpinA3N, in the hippocampus of temporal lobe epilepsy mice induced by KA was significantly increased, and it promoted neuroinflammation and seizure by activating NF-κB signaling pathway, suggesting that Serpin family is closely related to epilepsy. 30 Therefore, it is worthy to further explore if initial seizures-induced inflammation elicits elevation of blood Serpin E1 and if its long persistence is implicated in the development or maintenance of DRE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Serpina3n was reported to be primarily dysregulated in astrocytes in a kainic acid (KA)-induced temporal lobe epilepsy (TLE) mouse model; its overexpression promoted, whereas its KD attenuated pro-inflammatory cytokine expression and astrocyte reactivity in the hippocampus. 64 Taken together, these animal data prompt us to hypothesise that astrocytederived Serpina3n/SERPINA3 plays a strong pro-inflammatory role in neurological diseases/injuries; its experimental overexpression in astrocytes is sufficient to initiate inflammatory responses even in the homeostatic brain.…”
Section: Serpina3n/serpina3 and Inflammation With A Focus On Preclini...mentioning
confidence: 96%
“…Serpina3n was reported to promote neuronal survival through inhibiting granzyme B 27,53 or clusterin 54 in ischaemic brain injury, whereas it promoted neuronal survival in traumatic brain injury by inhibiting leukocyte elastase 55 or matrix metalloproteinase 2 (MMP2), 61 but not granzyme B. In sharp contrast, astrocytederived Serpina3n was shown to aggravate neuronal injury and death in chemical-induced neurotoxic injury 60 and epileptic injury 64 presumably through promoting neuroinflammation as discussed above. These seemingly contradictory data suggest that the role of Ser-pina3n in neuronal death/survival depends on its cellular sources and/or injury types.…”
Section: Role and Mechanisms Of Serpina3n/ Serpina3 In Neuronal Death...mentioning
confidence: 97%
“…After washing, the tissues were reacted with Cy3-conjugated immunoglobulin G (IgG) and fluorescein isothiocyanate (FITC)-conjugated IgG antibody for 2 h. The sections were observed using a confocal microscope (LSM700, Carl Zeiss, Thornwood, NY, USA). Sirt3-GFAP double-positive cells were counted in the CA1 subfield of the hippocampus of patients with TLE with HS to analyze the changes of Sirt3 expression within reactive astrocytes (Liu et al, 2023).…”
Section: Immunofluorescence Staining In Paraffinized Human Hippocampa...mentioning
confidence: 99%